Zwitterionic polymer/ polydopamine coating reduce acute inflammatory tissue responses to neural implants - Golabchi, Asiyeh (Biomaterials, 2019)
The inflammatory brain tissue response to implanted neural electrode devices has hindered the longevity of these implants. Zwitterionic polymers have a potent anti-fouling effect that decreases the foreign body response to subcutaneous implants. In this study, we developed a nanoscale anti-fouling coating composed of zwitterionic poly (sulfobetaine methacrylate) (PSB) and polydopamine (PDA) for neural probes. The addition of PDA improved the stability of the coating compared to PSB alone, without compromising the anti-fouling properties of the film. PDA-PSB coating reduced protein adsorption by 89% compared to bare Si samples, while fibroblast adhesion was reduced by 86%. PDA-PSB coated silicon based neural probes were implanted into mouse brain, and the inflammatory tissue responses to the implants were assessed by immunohistochemistry one week after implantation. The PSB-PDA coated implants showed a significantly decreased expression of glial fibrillary acidic protein (GFAP), a marker for reactive astrocytes, within 70 μm from the electrode-tissue interface (p<0.05). Additionally, the coating reduced the microglia activation as shown in decreased Iba-1 and lectin staining, and improved blood-brain barrier integrity indicated by reduced immunoglobulin (IgG) leakage into the tissue around the probes. These findings demonstrate that anti-fouling zwitterionic coating is effective in suppressing the acute inflammatory brain tissue response to implants, and should be further investigated for its potential to improve chronic performance of neural implants.